2007
DOI: 10.1213/01.ane.0000284705.34629.c5
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Attenuates Bone Cancer Pain and Inhibits Spinal Interleukin-1β Expression in a Rat Model

Abstract: The data suggest that EA alleviates bone cancer pain, at least in part by suppressing IL-1beta expression. The results support the clinical use of EA in the treatment of cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 37 publications
5
48
0
1
Order By: Relevance
“…A previous study demonstrated that EA inhibits bone cancer-caused IL-1β expression and bone cancer pain [24]. IL-1β also promotes NR1 phosphorylation [6].…”
Section: Fig (5)mentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study demonstrated that EA inhibits bone cancer-caused IL-1β expression and bone cancer pain [24]. IL-1β also promotes NR1 phosphorylation [6].…”
Section: Fig (5)mentioning
confidence: 95%
“…A symmetrical biphasic wave was delivered to each electrode so that it was alternately positive and negative to stimulate the bilateral needles. To minimize discomfort, stimulation intensity was gradually increased over a period of 2 min to 2 mA, which we have found to be the maximum level that can be tolerated by unrestrained rats [24]. During EA treatment, each rat was placed under an inverted clear plastic chamber approximately 5" × 8" × 11" and neither restrained nor given any anesthetic.…”
Section: Electroacupuncturementioning
confidence: 99%
“…[22][23][24][25][26] A recent study also showed that electroacupuncture alleviates bone cancer pain by suppressing spinal expression of interleukin-1b in glial cells that are involved in the spinal transmission and processing of noxious inputs from the peripheral sites and facilitates pain. 27 It is conceivable that acupuncture reduces BIPN symptoms by suppressing activities of glial cells and stimulating neurohormonal pathways, which increases endorphine release and reduces proinflammatory cytokines. 28 Lastly, animal studies suggest that acupuncture might stimulate nerve growth factors and accelerate nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…At this point in time, there is not convincing evidence that acupuncture signiicantly reduces cancer pain in the human literature. That being said there are several studies using animal models of cancer bone pain that suggest that acupuncture can reduce bone tumor-induced pain including osteosarcoma-induced pain [1,106,107]. The animal data suggest that electroacupuncture can alleviate bone cancer pain, at least in part by suppressing IL-1β expression and by altering nerve innervation and the vasculature of osteosarcoma.…”
Section: Complementary/alternative Therapiesmentioning
confidence: 99%